Resistance to bacterial infection, complication occurring after cardiac surgery - Hamasaeed, Payman Akram (Cellular and Molecular Biology, 2020)
To analyze the occurrence of resistant bacterial infection in patients undergoing cardiac surgery hospitalized in the surgical specialty hospital, in Erbil city, Iraq. A prospective study was done on a total of 138 patients operated and hospitalized in an intensive care unit and surgical wards. Bacterial isolates identification was done according to cultural characteristics, microscopic examination, some biochemical tests, analytic Profile Index 20E& API Staph, confirmed with VITEK® 2 compact system (BioMérieux). Antimicrobial susceptibility for disc diffusion tested to 17 antimicrobial agents. Resistance isolates were confirmed phenotypically for carbapenemase by Rapidec Carba NP Test (bioMe´rieux SA, Marcy-l’E´toile, France) for ESBLs producers by ESBL screening test VITEK 2 system. Molecularly blaIMP blaTEM, blaKPC, AmpC and blaCTX-M were detected by PCR. In 134 patients, 28.3% of patients got infected post-operatively. The most frequent source of isolation was from ICU patients (75%). Isolated bacteria included gram-positive 29 (54.7%) and gram-negative bacteria 24 (45.3%). Most frequently: Staphylococcus aureus (24.4%), each of pseudomonas aeroginosa, Klebsiella pneumonia (15.1%), Streptococcus spp. (11.3%), Escherichia coli (9.4%). Whereas included Coagulase Negative Staphylococci species (CoNS) (13.2%) and Enterococci species (5.7) Statistical analysis showed significantly higher sensitive isolates as compared with resistance isolates. Resistance to Carbapenems calss was 18.9% and Cephalosporins class 41.5% of isolates. The antimicrobial resistance pattern indicated that MDR bacterial isolates (81.1%) were widespread. Of the 34 phenotypically ESBL positive isolates, the ESBL genes (AmpC, blaCTX-M, and blaTEM) were amplified in 7(20.6), 6(17.6) and 6(17.6) isolates respectively. Out of 8 K. pneumonia (37.5%) harboring both blaAmpC and bla-CTX-M genes, while 6(75%) carries blaTEM. The blaCTX-M gene was found in only 1 (12.5%) out of 8 isolates of P. aeruginosa. While blaAmpC genotyping revealed that 1(7.7%) out of 13 Staph. aureus isolates were harboring it. Finally, 3(60%) out of 5 E. coli isolates harboring both AmpC and bla-CTX-M genes. Cardiac surgery patients wound show increasingly emerging strains of ESBL-producing gram-negative bacteria K. pneumonia, P. aeruginosa and E. coli especially patients prolonged in the intensive care unit.